2021
DOI: 10.1155/2021/1622375
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii Ameliorates Dextran Sulfate Sodium‐Induced Ulcerative Colitis in Mice by Regulating NF‐κB and Nrf2 Signaling Pathways

Abstract: Saccharomyces boulardii (S. boulardii) is a probiotic yeast that is widely used to treat gastrointestinal disorders. The present study is aimed to explore the therapeutic effects of S. boulardii on dextran sulfate sodium- (DSS-) induced murine ulcerative colitis (UC) and illustrate the mechanisms of action. C57BL/6 mice were administered S. boulardii (105 and 107 CFU/ml, p.o.) for 3 weeks and then given DSS [2.5% ( w / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
(40 reference statements)
4
16
0
Order By: Relevance
“…Furthermore, anti-inflammatory cytokines such as IL-10, IL-27 and IL-35 can be expressed and produced by Lactobacillus and non-pathogenic Escherichia coli ( Barra et al, 2020 ). Saccharomyces boulardii can ameliorate DSS-induced colitis in mice by inhibiting the activation of nuclear factor kappa-B (NF-κB) signaling pathway and inhibiting the release of pro-inflammatory cytokines ( Gao et al, 2021 ). Notably, increased short-chain fatty acids generation in response to probiotics can decrease TNF-α and IL-12, increase IL-10, inhibit NF-κB signaling pathway, and produce anti-inflammatory effects ( Säemann et al, 2000 ; Segain, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, anti-inflammatory cytokines such as IL-10, IL-27 and IL-35 can be expressed and produced by Lactobacillus and non-pathogenic Escherichia coli ( Barra et al, 2020 ). Saccharomyces boulardii can ameliorate DSS-induced colitis in mice by inhibiting the activation of nuclear factor kappa-B (NF-κB) signaling pathway and inhibiting the release of pro-inflammatory cytokines ( Gao et al, 2021 ). Notably, increased short-chain fatty acids generation in response to probiotics can decrease TNF-α and IL-12, increase IL-10, inhibit NF-κB signaling pathway, and produce anti-inflammatory effects ( Säemann et al, 2000 ; Segain, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the various factors, the role of gut microbiota has received much attention 18 . Moreover, considerable evidence indicates that probiotics administration could attenuate UC-associated symptoms and inflammation, presumably through modulating the gut microbiota (Table 1) [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Meanwhile, emerging studies also reported that postbiotic application could reduce the risk of development of UC 31,[33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [ 182 ] studied Saccharomyces boulardii , a probiotic yeast resistant to low pH and highly tolerant to bile acids, in mice models of UC by regulating the NF-κB and Nrf2 signaling pathways. The authors used a DSS-induced C57BL/6 mice model of colitis and, after treatment with 105 and 107 CFU/mL, p.o.…”
Section: Future Perspectivesmentioning
confidence: 99%